The Dark Side of Social Media: Content Effects on the Relationship Between Materialism and Consumption Behaviors - Pellegrino, Alfonso; Abe, Masato; Shannon, Randall (Frontiers in Psychology, 2022)
This study contributes to the emerging literature on the negative effects over consumption that social media users may develop as a consequence of being engaged on social media platforms. The authors tested materialism's direct and indirect impacts on compulsive, conspicuous, and impulsive buying, adding two novel mediators: attitudes towards social media content and social media intensity. The study uses a convenience sample of 400 Thai social media users analysed using structural equation modelling. The results confirmed the well-established positive relationships between materialism and each of the three-negative consumption behaviours also in the social media domain. A novel finding showed the important role played by social media intensity which was found to be a strong predictor of each of the three negative consumption behaviours and it was also found to significantly mediate the relationship between materialism and the three-negative consumption behaviors. An additional contribution of the study was found on the role of attitudes which, contrary to what is commonly believed, were often not significant in predicting any negative behavior.